COMPARISON OF ULTRASOUND EVALUATION OF PATIENTS OF OBSTRUCTIVE JAUNDICE WITH ENDOSCOPIC RETROGRADE CHOLANGIO-PANCREATOGRAPHY FINDINGS - Farrukh, Syed Zea-ul-Islam; Siddiqui, Arif Rasheed; Haqqi, Syed Afzal; Muhammad, Asif Jan; Dheddi, Abdul Samad; Niaz, Saad Khalid (Journal of Ayub Medical College Abbottabad, 2016)
Background: Ultrasonography has proven to be quite effective in differentiating hepatocellular from obstructive cause of jaundice in various studies. This study was conducted with the aim to determine the efficacy of ultrasonography and Endoscopic Retrograde Cholangio-Pancreatography (ERCP) in the diagnosis of obstructive reason of jaundice. Methods: In this descriptive case series, 200 patients with >15 years age of either gender with cholestatic liver enzymes were included, i.e., those patients who had an ultrasound prior to ERCP at the department of gastroenterology of Patel Hospital, Karachi. Patients known to have liver disease with cholestatic jaundice had imaging other than ultrasound were excluded. The results of ultrasonography and ERCPs were compared in particularly looking for the cause of obstruction. Results: Out of total 200 patients, mean age was 41.22±12.46 years with 107 (53.5%) females. Ability of ultrasound in correctly diagnosing obstructive reason for stone CBD was found to be 72.5%, dilated CBD without reason 41.7%, proximal obstruction, 63.15%, distal CBD obstruction 60%, and sludge 66.7%. Overall ability of ultrasound in correctly diagnosing the cause of obstruction was 64.17%. Conclusion: Ultrasound is recommended as the initial examination, which provides a guide to choose patients for either a more advanced non-invasive imaging like MRCP or to an invasive procedure like ERCP. Keywords: Obstructive Jaundice; Ultrasound, Endoscopic Retrograde Cholangiopancreatography